Peruraian Anaerobik Termofilik Palm Oil Mill Effluent dengan Variasi Konsentrasi Substrat - Roberty Wisnu Alvania Kartika; Nadiya Salsabila Desman; Irfan Dwidya Prijambada (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2022)
High utilization of palm oil in Indonesia corresponds to palm oil mill effluent (POME). The POME has chemical oxygen demand (COD) of up to 100.000 mg/L, which can pollute the ecosystem if not adequately treated. One of the methods to manage POME is anaerobic thermophilic digestion. The advantage of this method is the production of methane gas which is a form of alternative energy. Substrate concentration affects anaerobic digestion. This preliminary experiment aims to evaluate the performance of anaerobic thermophilic digestion on various POME concentrations at 55 °C. The anaerobic digestion was run with 16.000, 11.000 and 5.000 mg sCOD/L substrate concentrations. Digested cow manure (DCM) was used as inoculum. The process was running in a continuous system after 7-days of acclimatization of the batch system. The result shows that 16.000 and 11.000 mg sCOD/L concentrations produced more methane, but the methane yield was not statistically significant with the Tukey test (p=0,05). The POME with a 5.000 mg sCOD/L concentration produced less methane and plummeted after day 85. The lower methane production at lower substrate concentration was due to the low sCOD availability and high volatile fatty acid (VFA) accumulation which inhibited the methane production.